The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1103/physreve.96.052703
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of liquid crystalline dimer mixtures exhibiting the nematic and twist-bend nematic phases

Abstract: © 2017 American Physical Society. This is an author produced version of a paper published in Physical Review E. Uploaded in accordance with the publisher's self-archiving policy.eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
(43 reference statements)
3
21
0
Order By: Relevance
“…63,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] In addition to this, it has been shown that when the dimer is mixed with standard calamitics the resultant mixture can also show N TB phases, as well as exhibit distinctive changes in elastic constants. [96][97][98][99] The transitions for the pure CB7CB were measured as Iso 116 1C N 102 1C N TB , in agreement with literature values. 63,67,90 CB7CB has been shown to have a net positive De, due to the dominant effect of the longitudinal dipole moment of the ''hairpin'' conformer over the transverse dipole of the ''banana'' conformer ( Fig.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…63,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] In addition to this, it has been shown that when the dimer is mixed with standard calamitics the resultant mixture can also show N TB phases, as well as exhibit distinctive changes in elastic constants. [96][97][98][99] The transitions for the pure CB7CB were measured as Iso 116 1C N 102 1C N TB , in agreement with literature values. 63,67,90 CB7CB has been shown to have a net positive De, due to the dominant effect of the longitudinal dipole moment of the ''hairpin'' conformer over the transverse dipole of the ''banana'' conformer ( Fig.…”
Section: Methodssupporting
confidence: 84%
“…They exhibit values of k 11 /k 33 that are significantly higher than unity, 54,57,60,69,72,76,79,92 where standard calamitics typically exhibit k 11 /k 33 between 0.6 and 0.8. [93][94][95] It has also been shown that doping a standard calamitic liquid crystal with a bent-core or dimeric material can imbue the mixture with some similarly unusual elastic properties 56,92,[96][97][98][99] while still showing a nematic phase. For example, Parthasarathi et al 97 showed that binary mixtures of the bent dimer CB7CB with calamitic material 7OCB at certain temperatures exhibits k 11 /k 33 4 5.…”
Section: Ehdi In Bent Cores and Dimersmentioning
confidence: 99%
“…and its longer homologues (M. Cestari et al 2011;Nerea Sebastián et al 2016;Babakhanova et al 2017;Nerea Sebastián et al 2014;Robles-Hernández et al 2015;Yun et al 2015;Parthasarathi et al 2016;Robles-Hernández et al 2016;N. Sebastián et al 2017;Trbojevic, Read, and Nagaraj 2017).…”
mentioning
confidence: 99%
“…Another phase of interest in recent years is the Twist Bend Nematic (N TB ) [155,156,158,[202][203][204][205]. As the N TB phase forms relatively periodic optical structures, there has been interest in using them for the application of diffractive beam steering devices [206][207][208].…”
Section: Nematic Twist Bendmentioning
confidence: 99%